Research Progress in the Treatment of Complications and Sequelae of COVID-19 - Wang, Jinpeng; Zhu, Kuoyun; Xue, Yuchuan; Wen, Guangfu; Tao, Lin (Frontiers in Medicine, 2021)
With the improvement in the understanding of COVID-19 and the widespread vaccination of COVID-19 vaccines in various countries, the epidemic will be brought under control soon. However, multiple viruses could result in the post-viral syndrome, which is also common among patients with COVID-19. Therefore, the long-term consequences and the corresponding treatment of COVID-19 should be the focus in the post-epidemic era. In this review, we summarize the therapeutic strategies for the complications and sequelae of eight major systems caused by COVID-19, including respiratory system, cardiovascular system, neurological system, digestive system, urinary system, endocrine system, reproductive system and skeletal complication. In addition, we also sorted out the side effects reported in the vaccine trials. The purpose of this article is to remind people of possible complications and sequelae of COVID-19 and provide robust guidance on the treatment. It is extremely important to conduct long-term observational prognosis research on a larger scale, so as to have a comprehensive understanding of the impact of the SARS-CoV-2 on the human body and reduce complications to the greatest extent.